The Implementation of Role-Playing Method to Enhance Self-Confidence at Taman Kanak-Kanak Islam Ahsan Jambi City - Siti Sulthonah Hana Mahana Nur Hani'am Mari'a; Raoda Tul Jannah Maruddani; Kaspul Anwar; Mardiana Mardiana; Mastikawati Mastikawati; Fitriah Fitriah (Universitas Muhammadiyah Enrekang, 2024)
This study aims to enhance the self-confidence of young children at Taman Kanak-Kanak Islam Ahsan in Jambi City through the application of role-playing methods. Based on initial observations conducted on January 15-19, 2024, it was found that aspects of self-confidence development, including self-belief, Tidak mudah putus asam, objectivity, responsibility, and rationality, were still underdeveloped. Among the 12 children observed, all showed a lack of self-confidence (100%), 10 children were less Tidak mudah putus asatic (80%), only 5 children demonstrated objectivity and responsibility (40% each), and 7 children displayed rational and realistic thinking (60%). This research employed Classroom Action Research (CAR) using the Kemmis & McTaggart model with a cycle-based approach involving planning, action, observation, and reflection. The results indicated that implementing the role-playing method effectively increased the children’s self-confidence. Throughout Cycles I and II, there was a noticeable increase in the number of children categorized as